2020
DOI: 10.1016/j.urology.2019.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Anatomy of the Puboprostatic Ligament for the Safe Guidance for the Prostate Surgery

Abstract: OBJECTIVE To provide the anatomy of the puboprostatic ligament and related structures to save urogenital competence after prostatectomy. MATERIALS AND METHODS Pelvic areas of 31 adult cadavers were dissected to figure out the shape, number, and location of the puboprostatic ligaments. RESULTS The puboprostatic ligament was the most important support structure between the pubic bone and prostate gland. Puboprostatic ligaments were bilaterally single (61.3%), bilaterally double (19.4%), or mixed (19.4%). Ligamen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Recent findings, derived from human cadaveric studies, indicate that PV/PPL originates both from the visceral endopelvic fascia and the detrusor apron ( 35 ). Choi et al observed in a human cadaveric study ( n = 31) that PPLs were bilaterally single (61.3%), bilaterally double (19.4%), or mixed (19.4%) prevalent ( 39 ). The authors postulate that bilateral double PPLs are likely to result in urogenital competence ( 39 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent findings, derived from human cadaveric studies, indicate that PV/PPL originates both from the visceral endopelvic fascia and the detrusor apron ( 35 ). Choi et al observed in a human cadaveric study ( n = 31) that PPLs were bilaterally single (61.3%), bilaterally double (19.4%), or mixed (19.4%) prevalent ( 39 ). The authors postulate that bilateral double PPLs are likely to result in urogenital competence ( 39 ).…”
Section: Resultsmentioning
confidence: 99%
“…Choi et al observed in a human cadaveric study ( n = 31) that PPLs were bilaterally single (61.3%), bilaterally double (19.4%), or mixed (19.4%) prevalent ( 39 ). The authors postulate that bilateral double PPLs are likely to result in urogenital competence ( 39 ). Due to the close relationship to the DVC and anterior bladder, identification of the PPL is easily appreciated in small/normal-sized prostates.…”
Section: Resultsmentioning
confidence: 99%